Valorization of wheat bread waste and cheese whey through cultivation of lactic acid bacteria for bio-preservation of bakery products. (15th February 2023) - Iosca, Giovanna; Turetta, Monica; De Vero, Luciana; Bang-Berthelsen, Claus Heiner; Gullo, Maria; Pulvirenti, Andrea
Abstract: In this work, three lactic acid bacteria (LAB) strains, specifically, Lactiplantibacillus plantarum UMCC 2996, Furfurilactobacillus rossiae UMCC 3002, and Pediococcus pentosaceus UMCC 3010, were tested in new bread-whey media composed by wheat bread and sweet cheese whey, designed as an alternative to the conventional MRS medium. The medium resulting from hydrolysis with amylase and neutrase (AN) was considered the best for the growth of all the strains. This medium was particularly optimal for the strain F. rossiae UMCC 3002, which showed an increase in growth of 114% compared to that in MRS medium. Additionally, the bio-preservative ability of the selected LAB was assessed in pectin-based coated sliced bread inoculated with Aspergillus flavus ITEM 7828, Penicillium paneum ITEM 1381, and Aspergillus niger ITEM 7090 . Different LAB strain behavior was observed towards the specific molds. A good bio-preservation activity was shown from F. rossiae UMCC 3002 against A. flavus ITEM 7828 with results compared to the protection by ethanol treatment. The results obtained in this study suggest a novel strategy for the cultivation of selected starters with a bio-protection activity by valorizing bread waste and cheese whey by-products, in a circular economy perspective. Highlights: Bread waste and cheese whey can be valorized through cultivation of lactic acid bacteria (LAB). Bread-whey medium is an alternative to the conventional MRS medium. Selected LAB have bio-preservation activity against molds. Edible pectin-based coating with LAB can be employed for bread treatment. LAB starters can be applied for bio-preservation of bakery-products.